Analisis Kapasitas dan Tekanan Kerja Kompresor Airman Model SAS37S-57 Untuk Mengurangi Drop Pressure Pada Line Effervescent PT. Bintang Toedjoe (Jurnal Ilmiah Teknik Mesin, 2025)
A compressor is a device that has a function to drain and add energy (pressure) to its working fluid, which in this case is a compressible fluid, namely compressed air. The compressed air system at PT Bintang Toedjoe site Cikarang is a compressor utility facility that supports critical support for the production operation of the effervescent line. This compressor is needed to supply pressurized air in a storage tank or storage tank and then flowed to the production process room using pipe installations and accessories so that the need for compressed air over a considerable distance can be flowed according to the needs of compressed air on the effervescent line user machine, namely the filling and packaging machine. The need for compressed air at PT Bintang Toedjoe is met by a rotary category positive displacement compressor in the form of a compressor in the form of a helical screw compression. Given the importance of improving the quality of this compressed air system, it is necessary to conduct an analysis of the compressor's capacity and working pressure to prevent and reduce the occurrence of drop pressure in the production of the effervescent line. From the calculation results, the required air capacity of 23.05 m3/min is obtained theoretically based on the consumption specifications of each user's machine. For the selection of compressors, it is a type of oil injected screw compressor